Network Flow of Campaign Discourses and News Frames: The Changing Fortunes of Twitter/X as a Conduit for Frame-Building - Auwal, Ahmad Muhammad; Ersoy, Metin; Zakari, Muhammad Jamil; Dalhatu, Sadiya (Routledge Journals, Taylor & Francis Ltd, 2024)
Periodic changes continue to impact the fortunes of Twitter as a political communication and news-sharing platform, particularly among diverse individual and institutional African users. Yet few studies provide empirical insights into Twitter's changing role in campaign communication and its influence on news frame-building across the region, mainly in Nigeria. This study bridges the gap by analysing n = 763 tweets to determine how the political campaign discourse strategies in the tweeting activities of two prominent candidates influenced the news frame-building practices of mainstream newspapers during the four months of Nigeria's 2019 presidential campaign. Findings affirm that the Twittersphere served as a playground where candidates deployed diverse discourse frames correlating with political agendas to show their intent to integrate Twitter into their campaign communication strategies. Moreover, the candidates' tweets contribute to the journalistic frame-building process, although the newspapers tend to focus more on frame-setting than frame-sending due to the dynamic nature of journalistic content production across individual news outlets.
Keywords: campaign discourses; frame-sending; frame-setting; journalistic frame-building; network of frames; political Twittersphere